Fragile Balances: Turkish Foreign Policy on the Sovereignty of the Dodecanese Islands (1940-1947) - PAPUÇÇULAR, HAZAL (Routledge Journals, Taylor & Francis Ltd, 2-4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxon, England, 2018)
The Dodecanese Islands became a subject of diplomatic negotiations both during and after World War II. This article examines the position of Turkish foreign policy on the sovereignty of the islands. It argues that the analysis of the subject necessitates a multi-faceted approach which takes both the concerned parties' stance and Turkey's post-war international status into consideration. This study shows that Britain and the US frankly favoured the Greek claims after 1940. Accordingly, it asserts that in the post-war period, Turkey constituted its diplomacy over the Dodecanese based on the rising Soviet threat against which it sought support from the Western powers. It also shows that Ankara sometimes made attempts to intervene in the process regarding the Dodecanese although they were short-lived and inconclusive.
Keywords: The Dodecanese Islands; Turkish foreign policy; Aegean Sea; Second World War; early Cold War